Rancang Bangun Administrative Workflow System Rekrutmen Dan Seleksi Pada STIKOM Surabaya - Wijaya, Adrianus; Tjandrarini, A.B.; Susilo, Tegar Heru (Jurnal JSIKA, 2014)
Abstract: The process of recruitment and selection in STIKOM Surabaya which depends on hard copy based processing, is having 4 (four) potential risks found in its administrative process, namely: Storage requirement, Extensive resources to file and search for documents, security risk, and Delay risk. To reduce or avoid such risks mentioned above, a website will be developed as a solution that comes with the ability to store document files in order to keep unauthorized parties from accessing the applicants documents, thus solving the storage requirement risk. the website will also implement administrative workflow system to direct the process or task to authorized and correct people, to keep recruitment and selection process run as usual, despite the use of paper is eliminated. based on the test result, the developed product already can solve risks mentioned above, but must be developed again on several things, such as design of the web, and the improvement of the products functions.